APPLYING ENGAGE, STUDY, ACTIVATE PROCEDURE IN TEACHING GENRE WRITING - Ginting, Siti Aisah (Jurnal Bahasa Lingua Scientia, 2011)
Teaching writing requires teachers to apply a suitable method which involves students mentally and physically. ESA Procedure has some unique benefit for both teachers and students since teachers begin the lesson with engaging students to the material to be taught and the classroom situation. ESA, with all its types, can be used to teach students to write texts in different genres and levels of difficulties. By this procedure, teachers can explore students? readiness to begin writing whereas students themselves have opportunities to develop their knowledge through the information obtained during the teaching-learning process. In short, ESA is one procedure that should be applied by teachers in teaching genre writing.